DEMOGRAPHIC INDICATORS FOR THE STATISTICAL STUDY OF SMALL BUSINESS - Vladimir I. Kuznetsov (Статистика и экономика)
For small enterprises high mobility, theshort period of existence is characteristic.Possibility of application of demographicindicators for the characteristic of processes of the birth and death of enterprises isconsidered. Criteria for the characteristic of a condition of enterprises are offered.